The Effectiveness of Massage Therapy in Treating Sports-Related Muscle Injuries: An Evidence-Based Systematic Review and Meta-Analysis - Santa Nunut Hutasoit; Mona Benedikta Ambarita; Tary Aprilyani Sitorus (IGI Active Living and Health Insight, 2026)
Purpose of the study: Sports-related muscle injuries, including strains, tears, contusions, and delayed-onset muscle soreness (DOMS), account for up to half of all sports injuries and are a major cause of time-loss in athletes. Massage therapy is widely used as an adjunctive treatment, yet its efficacy across injury types and athletic populations remains variably reported. To systematically evaluate and quantify the effectiveness and safety of massage therapy for sports-related muscle injuries in adult athletes, and to explore dose–response relationships, moderating factors, and remaining evidence gaps. Materials and methods: This systematic review and meta-analysis followed PRISMA 2020 guidelines. PubMed, Scopus, Web of Science, EMBASE, and CENTRAL were searched from inception to 31 October 2024. Eligible studies included randomized controlled trials, quasi-experimental studies, and prospective cohorts evaluating massage therapy for sports-related muscle injuries in adults, compared with placebo, usual care, other therapeutic modalities, or no treatment. Primary outcomes were pain, range of motion (ROM), functional recovery, return-to-play, and muscle damage biomarkers (e.g. serum creatine kinase [CK]). Risk of bias was assessed using RoB 2 for trials and Newcastle–Ottawa Scale for observational studies. Random-effects meta-analyses were conducted; heterogeneity was quantified with I², and certainty of evidence graded using GRADE. Results: Forty-seven studies (n = 3,284; 19 countries; 2000–2024) met inclusion criteria; 42 were pooled meta-analytically. Massage therapy significantly reduced pain versus control (standardized mean difference [SMD] = −0.87; 95% CI −1.12 to −0.62; p < 0.001), improved ROM (SMD = 0.64; 95% CI 0.38 to 0.91; p < 0.001), and reduced serum CK (SMD = −0.64; 95% CI −1.04 to −0.25; p = 0.001). Effects on DOMS were large, peaking 48–72 h post-intervention (SMD up to −1.51). Deep tissue massage showed greater pain reduction than Swedish, sports-specific, or myofascial techniques (p = 0.008). Bi-weekly protocols with 40–60 min sessions were associated with the most favorable outcomes. Team sport and strength-training athletes exhibited the largest performance and recovery benefits. Adverse events were rare and mild; no serious events were reported. Evidence certainty was rated high for pain and DOMS, and moderate for ROM and CK. Conclusions: Massage therapy is an effective, safe, and evidence-based complementary intervention for sports-related muscle injuries, particularly for pain relief, DOMS attenuation, and functional recovery acceleration. Deep tissue massage delivered bi-weekly for 40–60 minutes appears optimal. Integration of massage therapy into multimodal rehabilitation and return-to-play strategies is supported, although further research is needed on comparative effectiveness, dose–response, and long-term outcomes.